2005
DOI: 10.1152/ajpcell.00458.2004
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 in oncogenic transformation, cancer, and metastasis

Abstract: Caveolae are 50- to 100-nm omega-shaped invaginations of the plasma membrane that function as regulators of signal transduction. Caveolins are a class of oligomeric structural proteins that are both necessary and sufficient for caveolae formation. Interestingly, caveolin-1 has been implicated in the pathogenesis of oncogenic cell transformation, tumorigenesis, and metastasis. Here, we review the available experimental evidence (gleaned from cultured cells, animal models, and human tumor samples) that caveolin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
525
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(544 citation statements)
references
References 117 publications
14
525
2
3
Order By: Relevance
“…Caveolin-1 interacts closely with the src family kinase (SFK), fyn, in linking integrins with ras-ERK signaling in the focal adhesion pathway as well as other SFKs [32,33]. Moesin is a member of the ERM (Ezrin/ Radixin/Moesin) family of proteins which have been shown to interact with src in adhesion-mediated signaling [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin-1 interacts closely with the src family kinase (SFK), fyn, in linking integrins with ras-ERK signaling in the focal adhesion pathway as well as other SFKs [32,33]. Moesin is a member of the ERM (Ezrin/ Radixin/Moesin) family of proteins which have been shown to interact with src in adhesion-mediated signaling [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This dual activity is typified in breast cancer, where the influence of caveolin-1 expression on disease progression appears both type and stage specific [35][36][37]. The use of cell lines derived from breast carcinomas [18,22,38] together with the development and study of caveolin-1 knockout mice [39][40][41] have concluded that the loss of caveolin-1 in mammary epithelial cells is sufficient to drive several pathological features of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [35][36][37] have used recombinant expression of caveolin-1 to restore caveolin-1 levels in various experimental cancer models in order to inhibit oncogenic signalling pathways, including the EGF-R/ERK cascade. Here we examined if the restoration of caveolin-1 in TAM-R cells through recombinant means was sufficient to inhibit EGF-R/ERK signalling, a key driver of the tamoxifenresistant phenotype in this cell model.…”
Section: Discussionmentioning
confidence: 99%
“…There is a constitutive process of endocytosis mediated by the internalization of the plasmalemmal invaginations, caveolae (20). Although caveolar internalization is responsible for transcytosis of albumin and other plasma proteins across the endothelial barrier, endocytosis may also have key functions in cell signaling (4,5,7,25). In the present study, we investigated the possibility that caveolae-mediated endocytosis is a determinant of endothelial cell proliferation and cell survival and thus regulates the integrity of the endothelial monolayer.…”
mentioning
confidence: 95%
“…Endocytosis was assayed by the uptake of albumin with FITC-BSA or TRITC-BSA as the tracer (24). In RLM-VEC treated with the MAPK p38 inhibitor SB-203580 (6,7,25) (Calbiochem, San Diego, CA), the drug (1-20 M) was incubated in increasing concentrations in confluent cell monolayers for 4 h at 37°C. Care was taken to avoid exposure to light during the uptake assay.…”
mentioning
confidence: 99%